Predictive value of 25-hydroxyvitamin D level in patients with coronary artery disease: A meta-analysis - Zhang, Hailing; Wang, Pei; Jie, Yu; Sun, Yimeng; Wang, Xiaoyan; Fan, Yu (Frontiers in Nutrition, 2022)
Background: A consensus has not been made about the predictive value of blood vitamin D level in patients with coronary artery disease (CAD). This meta-analysis aimed to assess the association between blood 25-hydroxyvitamin D level and adverse outcomes in patients with CAD. Methods: Two independent authors searched the articles indexed in PubMed and Embase databases until June 28, 2022. Cohort studies or post-hoc analysis randomized trials evaluating the value of 25-hydroxyvitamin D level in predicting cardiovascular or all-cause mortality, and major adverse cardiovascular events ([MACEs] including death, non-fatal myocardial infarction, heart failure, revascularization, stroke, etc.) were included. Results: The literature search identified 13 eligible studies for our analysis, including 17892 patients with CAD. Meta-analysis showed that the pooled adjusted risk ratio (RR) was 1.60 (95% confidence intervals [CI] 1.35–1.89) for all-cause mortality, 1.48 (95% CI 1.28–1.71) for cardiovascular mortality, and 1.33 (95% CI 1.18–1.49) for MACEs. Leave-out one study sensitivity analysis suggested that the predictive values of blood 25-hydroxyvitamin D level were reliable. Conclusions: Low blood 25-hydroxyvitamin D level is possibly an independent predictor of cardiovascular or all-cause mortality and MACEs in patients with CAD. Baseline 25-hydroxyvitamin D level may provide useful information in CAD patients.